The biology of coastal sand dunes - Maun, M. Anwar (Muhammad Anwar), 1935-2007 (Oxford University Press, 2009)
A concise but comprehensive introduction to the biology of coastal sand dunes. The emphasis in this book is on the organisms that dominate this predominantly marine environment, although pollution, conservation, management and experimental aspects are considered. - ;Coastal zones are becoming increasingly topical (and politically sensitive) as they face relentless pressures from urban expansion, recreational development, and sea level rise due to climate change. This timely book provides a comprehensive introduction to the formation, dynamics, maintenance, and perpetuation of coastal sand dune.